2000
DOI: 10.1253/jcj.64.653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Patients With Atrial Fibrillation

Abstract: In Japan, data on the epidemiological and clinical features of atrial fibrillation (AF) are rather sparse; even less data are available on the risk of thromboembolism in nonvalvular AF. The present study enrolled 19,825 patients who visited the cardiovascular clinics of the 13 hospitals in Hokkaido, Japan, between March and July 1995. The prevalence of AF, the clinical characteristics of AF patients, and the occurrence of ischemic events were examined during the 2 year follow-up period. The prevalence of AF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 20 publications
7
34
1
Order By: Relevance
“…7) However, the mean age of our patients was about 5 years older than theirs. Age is one of the most important risk factors for stroke, because the prevalence of other risk factors generally increases with age.…”
Section: Discussioncontrasting
confidence: 50%
“…7) However, the mean age of our patients was about 5 years older than theirs. Age is one of the most important risk factors for stroke, because the prevalence of other risk factors generally increases with age.…”
Section: Discussioncontrasting
confidence: 50%
“…[13][14][15][16][17][18] Meta-analysis on an intention-to-treat basis has confirmed that the risk of ischemic stroke is 61% lower in patients treated with anticoagulant therapy than in those treated with placebo therapy. 19) Epidemiological studies performed in Japan have shown that the annual rate of ischemic stroke in nonvalvular AF patients is 2.8-4.5%, 20,21) which is similar to that in Western studies. However, the observation period was relatively short (approximately 1-2 years) in these studies, and there have been few long-term investigations like the present study in which observation was continued for approximately 5 years.…”
Section: Discussionsupporting
confidence: 60%
“…In a hospital-based study, the prevalence of AF among outpatients was 14%. 7 In a population-based study, it was found that the prevalence of AF in a mixed group of men and women increased from 0.2% in persons aged 40 to 59 years to 2.5% in persons 80 years or older. 8 The results of our study are similar to those of that study.…”
Section: Women Both Sexesmentioning
confidence: 99%